Adaptasi Design Thinking dalam Revitalisasi Museum Ronggowarsito berbasis Interaktif dengan Pendekatan SMCR - Toto Haryadi; Godham Eko Saputro (Institut Seni Indonesia Yogyakarta, 2022)
Ronggowarsito is one of the iconic museums in Semarang. Like other museums, the classic problem of this museum is lack of visitors. Some factors that cause it such as bad management, the promotion and branding of museum which is poor of innovation, and also absence of collaboration with other parties such as academician, practician, and artist in creating interesting events. These various problems encourage the needs of museum revitalization creatively and innovatively and also up to date with technology and lifestyle nowaday. This research uses qualitative approach. Data are gained through observation, interview, documentation, and literature study methods. These data are used to design interactive-based museum revitalization product through design thinking and SMCR commnication to breakdown product contents. This research has a result an desktop-based interactive application called “KiosK Museum Ranggawarsita”. This product can present information in form of text, audio, and video interactively. This product can be developed further to success a program of museum management namely “Museum goes to school”, so that it will be a tool on museum introducing through academic visitations, seminars, and exhibition around city in Central Java.